Міжкультурна комунікація, дискурс та переклад - Кияк, Тарас; Kyiak, Taras (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Розглядається гіпотеза про присутність чинника дискурсу в процесі перекладу текстів різних жанрів. Категорія дискурсу впливає на переклад більшою чи меншою мірою, залежно від об’єкта перекладу в діапазоні «поезія – художня проза – науково-технічні тексти з низьким рівнем абстрактності – з середнім ступенем абстрактності – з високим рівнем абстрактності». Проаналізовано специфіку поняття культура. Hозглянуто взаємовплив та взаємозалежність однієї кільтури від іншої. Висвітлено історію всесвітньовідомого міста Кайнургардур. Обґрунтовано проблеми, що стосуються труднощів перекладу окремих творів. Виокремлено диференційні ознаки тексту та дискурсу. Звернуто увагу на відмінності дискурсу та міжкультурної комунікації. Окреслено низку труднощів, що виникають під час перекладу художніх творів однієї національної спільности на іншу мовою, базові етнічні концепти яких не збігаються. Доведено, що в різних культурах націй може суттєво відрізнятися терміносистема, яка їх обслуговує, передовсім, дефініції ключових концептів. Цікаво, що чим віддаленішою є культура, тим відміннішим є розуміння понять. Наголошено та тому, що дискурс виступає чинником і фіксатором міжкультурної комунікації, а також категорією перекладу.This article deals with the hypothesis about the discourse factor preserve of in the process of translation of different text genres. The translation depending on the object of translation in the “poetry – narrative literature – scientific and technical texts with the low abstraction level – with the medium abstraction level- with the high abstraction level” aspect. In this paper, specific features of the notion of culture have been analyzed. This article also deals with the interplay and interconnection between separate cultures. The history of the world-famous city of Kainurgardur has been recounted. Problems with respect to translation difficulties in some works have been identified. The distinctive features of text and discourse have been singled out.Attention is also devoted to the differences between textual and cross-cultural communication. The difficulties which arise in the process of translation from one language into another have been analyzed. It is affirmed that the main reason for this lies in the differences involving key ethnic concepts. It is demonstrated that in the cultures of different nations, there are significant differences between the terminological systems, and particularly in the definitions of key concepts. It is interesting to note that the more remote the culture is, t he more different is the understanding of the notions. It has been stressed that discourse is a factor in cross-cultural communication as well as a category of translation.
Interkultural Communication, Discourse and Translation
Keywords: дискурс; переклад; текст; абстрактність; жанр; ступінь; аспект; міжкультурна комунікація; discourse; translation; text; abstraction; genre; level; aspect; cross-cultural communication